Peradaban Sains dan Teknologi dalam Perspektif Islam - Abidzar Al-Ghifari Tahir; Afiat Mujahid; Anggreko Bio Sastrano; Muhammad Syamsul Munir (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Islamic civilization has played an important role in the development of global science and technology. From an Islamic perspective, knowledge is not merely used to meet practical human needs but also serves as a means of recognizing the greatness of Allah, developing the earth, and promoting human welfare. This paper aims to explain the concepts of science and technology from an Islamic perspective, identify the achievements of Muslim scholars that influenced the development of Western science, and describe Muslim figures who contributed to various scientific fields. This study employed a literature review method with a descriptive approach. Data were collected from books and literature concerning the history of Islamic civilization, the development of scientific knowledge, and the works of Muslim scholars. The findings indicate that the development of science and technology in Islamic civilization occurred through the early growth period, the golden age, the period of decline, and the modern revival. During the golden age, Muslim scholars produced significant works in medicine, mathematics, astronomy, physics, geography, geology, and chemistry. Scholars such as Al-Khwarizmi, Ibn al-Haytham, Al-Fazari, Al-Ya’qubi, Al-Jahiz, Jabir ibn Hayyan, Ibn Sina, and Al-Idrisi made contributions that later supported the development of modern science. Many of their works were translated and used as academic references in Europe. This study concludes that science and technology in Islam are founded on monotheism, morality, and human benefit. Understanding this scientific heritage is essential for strengthening intellectual confidence and encouraging Muslims to participate actively in the contemporary development of science and technology Peradaban Islam memiliki peran penting dalam perkembangan sains dan teknologi dunia. Ilmu pengetahuan dalam perspektif Islam tidak hanya digunakan untuk memenuhi kebutuhan praktis manusia, tetapi juga menjadi sarana untuk mengenal kebesaran Allah Swt., memakmurkan bumi, dan mewujudkan kemaslahatan umat. Penulisan ini bertujuan menjelaskan konsep sains dan teknologi dalam perspektif Islam, mengidentifikasi pencapaian ilmuwan Muslim yang memengaruhi perkembangan ilmu pengetahuan di Barat, serta mendeskripsikan tokoh-tokoh Muslim yang berkontribusi dalam berbagai bidang keilmuan. Penulisan menggunakan metode studi pustaka dengan pendekatan deskriptif. Data diperoleh dari buku dan literatur yang membahas sejarah peradaban Islam, perkembangan ilmu pengetahuan, serta karya ilmuwan Muslim. Hasil kajian menunjukkan bahwa perkembangan sains dan teknologi Islam berlangsung melalui periode pertumbuhan awal, masa keemasan, masa kemunduran, dan kebangkitan modern. Pada masa keemasan, ilmuwan Muslim menghasilkan berbagai karya penting dalam bidang kedokteran, matematika, astronomi, fisika, geografi, geologi, dan kimia. Tokoh-tokoh seperti Al-Khawarizmi, Ibnu Haitsam, Al-Fazari, Al-Ya’qubi, Al-Jahizh, Jabir bin Hayyan, Ibnu Sina, dan Al-Idrisi memberikan kontribusi yang menjadi dasar perkembangan ilmu pengetahuan modern. Berbagai karya tersebut diterjemahkan dan digunakan sebagai rujukan di Eropa. Kajian ini menyimpulkan bahwa sains dan teknologi dalam Islam berlandaskan tauhid, akhlak, dan kemanfaatan. Pemahaman terhadap warisan ilmiah tersebut penting untuk membangun kepercayaan diri serta mendorong umat Islam agar kembali aktif mengembangkan ilmu pengetahuan dan teknologi.